Skip to content

Commit

Permalink
Fix varaition of parameters example
Browse files Browse the repository at this point in the history
The example was wrong or incorrectly formatted in several ways.
I found a nicer example that still illustrates the method.
  • Loading branch information
wmboyles committed Apr 26, 2021
1 parent e837af0 commit 4c42e66
Show file tree
Hide file tree
Showing 2 changed files with 19 additions and 24 deletions.
43 changes: 19 additions & 24 deletions diffEq/higherOrder/nonHomeg/variationParameters_higherOrder.tex
Original file line number Diff line number Diff line change
Expand Up @@ -97,38 +97,33 @@ \subsubsection{Higher Order Variation of Parameters}
\begin{example}
Find the general solution to the equation
\begin{equation*}
x^3y''' + x^2y'' - 2xy' = x^3\sin{x} \text{, } x > 0
x^3y'' + x^2y' - xy = x^3\sin{x} \text{, } x > 0
\end{equation*}
given that $\left\{x, x^{-1}, x^2\right\}$ is the set of fundamental solutions.
given that $\left\{x, x^{-1}\right\}$ is the set of fundamental solutions.
\end{example}
\noindent
First we divide by $x^3$ to get a leading coefficient of 1.
\begin{equation*}
y''' + x^{-1}y''' - 2x^{-2}y' = \sin{x} \text{, } x > 0.
y'' + x^{-1}y' - x^{-2}y = \sin{x} \text{, } x > 0.
\end{equation*}
Next we calculate the $W(x)$ and each $W_i(x)$ for the fundamental solution set.
\begin{align*}
W[x,x^{-1}, x^2](x) &= \begin{vmatrix}
x & x^{-1} & x^2 \\
1 & -x^{-2} & 2x \\
0 & 2x^{-3} & 2
\end{vmatrix} = 6x^{-1} \\
W_1(x) &= (-1)^{3-1}W[x^{-1}, x^2](x) = (-1)^{2}\begin{vmatrix}
x^{-1} & x^2 \\
-x^{-2} & 2x
\end{vmatrix} = 3 \\
W_2(x) &= (-1)^{3-2}\begin{vmatrix}
x & x^{2} \\
1 & 2x
\end{vmatrix} = -x^2 \\
W_2(x) &= (-1)^{3-2}\begin{vmatrix}
\begin{alignat*}{3}
W[x,x^{-1}](x) &= \begin{vmatrix}
x & x^{-1} \\
1 & -x^{-2}
\end{vmatrix} = -2x^{-1}.
\end{align*}
1 & -x^{-2} \\
\end{vmatrix} &&= -2x^{-1} \\
W_1(x) &= (-1)^{2-1}W[x^{-1}] &&= (-1)^{1}\begin{vmatrix}
x^{-1}
\end{vmatrix} &&= -x^{-1} \\
W_2(x) &= (-1)^{2-2}W[x] &&= (-1)^{1}\begin{vmatrix}
x
\end{vmatrix} &&= x.
\end{alignat*}
Now we can calculate $y$.
\begin{align*}
y(x) &= x\int{\frac{(\sin{x})^3}{-6x^{-1}} \mathrm{d}x} + x^{-1}\int{\frac{(\sin{x})(-x^2)}{-6x^{-1}} \mathrm{d}x} + x^2\int{\frac{(\sin{x})(-2x^{-1})}{-6x^{-1}} \mathrm{d}x} \\
&= x\int{\left(\frac{-1}{2}x\sin{x}\right)\mathrm{d}x} + x^{-1}\int{\left(\frac{1}{6}x^3\sin{x}\right)\mathrm{d}x} + x^2\int{\left(\frac{1}{3}\sin{x}\right)\mathrm{d}x} \\
&= C_1x + c_2x^{-1} + C_3x^2 + \cos{x} - x^{-1}\sin{x}
y(x) &= x\int{\frac{(\sin{x})(-x^{-1})}{-2x^{-1}} \mathrm{d}x} + x^{-1}\int{\frac{(\sin{x})(x)}{-2x^{-1}} \mathrm{d}x} \\
&= \frac{x}{2}\int{\sin{(x)}\mathrm{d}x} - \frac{1}{2x}\int{x^2\sin{(x)}\mathrm{d}x} \\
&= \frac{x}{2}\left(-\cos{x}+C_1\right) - \frac{1}{2x}\left(2x\sin{x} - (x^2-2)\cos{x} + C_2\right) \\
&= C_1x + \frac{C_2}{x} -\frac{x\cos{x}}{2} - \sin{x} + \frac{(x^2-2)\cos{x}}{2x} \\
&= C_1x + C_2x^{-1} - \frac{\cos{x}}{x} - \frac{x\sin{x}}{x}.
\end{align*}
Binary file modified diffEq/main.pdf
Binary file not shown.

0 comments on commit 4c42e66

Please sign in to comment.